Androgen receptor polymorphism, testosterone levels, and prognosis in patients with acute myocardial infarction. Issue 2 (25th August 2021) - Wang, Anne; Flanagan, John; Arver, Stefan; Norhammar, Anna; Näsman, Per; Rydén, Lars; Mellbin, Linda G
Abstract: Aims: Low testosterone has been associated with cardiovascular disease in men but with contradictory findings. Testosterone bind to the androgen receptor and polymorphisms of the receptor gene such as CAG repeat length may affect transcriptional activity, possibly mitigating testosterone effects. The aims were to study the CAG repeat length and testosterone levels at four time points following a myocardial infarction (MI) and to analyse possible relationships between CAG repeat length and cardiovascular prognosis. Methods and results: Male patients admitted for acute MI ( n = 122) from the Glucose in Acute Myocardial Infarction study were included. Blood samples were drawn at four time points (day after admission, at discharge, and at 3 and 12 months post-infarction) for assessment of testosterone levels. Patients were followed for a median of 11.6 years. Cox regression analyses were performed for CAG repeat length by one unit increment and by > vs. ≤median for cardiovascular events and all-cause mortality. Median CAG repeat length was 20. There was no difference in testosterone levels at each time point when dividing the cohort into ≤ vs. >CAG repeat median (=20). There was no association between CAG repeat length either as a continuous or categorical variable in unadjusted and age-adjusted Cox analyses for cardiovascular events. While CAG >20 was associated with all-cause mortality in unadjusted analyses (hazard ratio 2.19, 95% confidence interval 1.13–4.22; P = 0.02), it did not remain significant following adjustment for age. Conclusion: CAG repeat length was not associated with testosterone levels or prognosis in men with acute MI. Graphical Abstract: